Effects of CO2-driven ocean acidification on early life stages of marine medaka (Oryzias melastigma) - J. Mu; F. Jin; J. Wang; N. Zheng; Y. Cong (Biogeosciences, 2015)
The potential effects of high CO2 and associated ocean acidification (OA) in marine fishes and other non-calcified organisms are less well understood. In this study, we investigated the responses of early life stages (ELS) of marine medaka (Oryzias melastigma) exposed to a series of experimental manipulation of CO2 levels. Results showed that CO2-driven seawater acidification (pH 7.6 and pH 7.2) had no detectable effect on hatching time, hatching rate, or heart rate of embryos. However, the deformity rate of larvae in the pH 7.2 treatment was significantly higher than that in the control treatment. There is no significant difference between the left and right otolith areas in each treatment. However, the average otolith area of larvae in the pH 7.6 treatment was significantly smaller than that in the control. Such alterations in the developmental abnormalities and otolith size of marine medaka larvae due to elevated-CO2 levels suggests that this species will be increasingly challenged by future OA. Further studies of the impacts of OA on marine fish to assess whether or not the environmental influence in one generation can affect the later life history and the phenotype of subsequent generations are needed.